Farewell to an old friend: chest X‐ray vs high‐resolution computed tomography in welders' lung disease. (2nd December 2013) - Tutkun, Engin; Abusoglu, Sedat; Yilmaz, Hinc; Gunduzoz, Meside; Evcik, Ender; Ozis, Türkan Nadir; Keskinkilic, Bekir; Unlu, Ali
Abstract Introduction Welder's lung disease originated from a mixed exposure to different kinds of metals and chemicals from welding fumes. Because of these various harmful effects, irreversible morphological changes may occur in all parts of the respiratory tract, airways and lung parenchyma. Parenchymal changes are the main lesions that define the severity of exposure. The grade of these lesions is the main criteria for compensation claims and the clinical threshold for the occupational health physician's decision making of work change in order to protect the worker's health. In this study, our aim was to compare the diagnostic performance of chest X‐ray (CXR) and high‐resolution computed tomography (HRCT) for welders' lung disease. Objectives Seventy‐four male welders aged between 25 and 55 years were enrolled to this study. Methods Clinical diagnoses were compared by CXR and HRCT. Same radiologists evaluated the scans without any knowledge about the medical history of the patient (double‐blinded evaluation). The agreement between radiologists was compared with Cohen's kappa statistics. Results The mean age for 74 welders was 40.7 years. The mean duration of exposure was 18.9 years. Although all were found to be nonpathological on the CXR, 27 mild nodular and nine mild linear opacities, five emphysematous changes, three ground glass infiltrates and one pleural thickening were detected by HRCT. Conclusions HRCT provides better diagnostic performance compared to CXR for the diagnosis of welders' lung disease.